The Influence of the Energy Sector on the Functioning of the Ukrainian Economy - Tomasz MOTOWIDLAK (Communications of International Proceedings, 2021)
The analysis carried out in the article serves to identify the main energy conditions for the functioning of the Ukrainian economy. Its purpose is to determine the impact of energy factors on the key performance parameters of this economy. As part of the study, the main problems in the functioning of the Ukrainian energy sector were identified, which made it possible to determine the sensitivity of the country's economy to energy factors. To achieve this goal, the method of analyzing the literature on the subject, the method of logical inference analysis, and the method of quantitative analysis in relation to energy factors conditioning the development of the Ukrainian economy were used. The results of the analyzes show that the energy conditions are a particularly important determinant of the functioning of the Ukrainian economy, which essentially determines the standard of living of the society and the political position of this country. The implementation of the long-term strategy of transforming Ukraine's energy sector, aimed at reducing its dependence on the Russian Federation and its sustainability, requires the implementation of a wide range of mechanisms that may positively influence the improvement of the economy's efficiency. The formulated conclusions may be used to indicate the main directions of Ukrainian energy reform in the context of the country's economic development.
Keywords: Economy of Ukraine; energy consumption of the economy of Ukraine; energy efficiency of Ukraine.